1998
DOI: 10.1051/lait:1998653
|View full text |Cite
|
Sign up to set email alerts
|

Casein micelle size in relation with casein composition and αs1, αs2, β and Κ casein contents in goat milk

Abstract: The relationship between micelle size and casein micelle composition was studied on 21 individual goat milks from animais homozygous for as1casein variants A, B 2 , C, E, F and O. A large variation in milk composition was obtained, as a sl secretion levels varied from 7.2 g-kg"! in A milks to none in 0 milks. Mean micelle size (MMS), determined by photon correlation spectroscopy, varied between samples from 192 nm to 287 nm. This was explained by the different aspects of the histograms of casein distribution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 16 publications
1
9
1
1
Order By: Relevance
“…Previously reported differences in mean size between α s1 -casein "null" and "strong" micelles were much more pronounced than those reported in the current study (216±26 vs. 207±35 nm); 280 vs. 200 nm (Pierre et al 1995) and 260 vs. 220 nm (Pierre et al 1998c). These previous studies included only three α s1 -casein "null" goats, compared to the present study including 150 homozygous α s1 -casein "null" goats.…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…Previously reported differences in mean size between α s1 -casein "null" and "strong" micelles were much more pronounced than those reported in the current study (216±26 vs. 207±35 nm); 280 vs. 200 nm (Pierre et al 1995) and 260 vs. 220 nm (Pierre et al 1998c). These previous studies included only three α s1 -casein "null" goats, compared to the present study including 150 homozygous α s1 -casein "null" goats.…”
Section: Resultscontrasting
confidence: 77%
“…The studies by Pierre et al (1995Pierre et al ( , 1998c concluded that the content of α s1 -casein was negatively correlated to the mean size of casein micelles in caprine milks.…”
Section: Resultsmentioning
confidence: 99%
“… # Source: Adapted and modified from Claeys et al ( 19 ) . Values derived from other references are represented by uppercase case letters: A, Roy et al ( 29 ); B, Nguyen et al ( 42 ), Pierre et al ( 43 ), and Pierre et al ( 44 ); C, Roy et al ( 29 ); D, Dalgleish ( 45 ), Wang et al ( 46 ), and Dewan et al ( 47 ); E, Pellegrini et al ( 48 ); F, Remeuf et al ( 49 ); G, Ahmad et al ( 50 ); H, Luo et al ( 51 ); I, Beaucher et al ( 52 ) . …”
Section: Comparative Compositions Of Cattle and Non-cattle Milksmentioning
confidence: 99%
“…In the last two decades research has continued to reveal the extensive casein polymorphism occurring in goat, but in spite of a large number of papers dealing with the wide heterogeneity of the casein fraction, the studies on the related impact are not so numerous. Several studies investigated Casensitive caseins (α s1 , α s2 and β), located within the micelles, establishing that they affect the technological properties of milk: strong alleles improve cheese-making and fat percentage: on the contrary, defective and null alleles make these features worse [15,40,60,66,67,75,76,85,89,91]. According to these findings genotypes at α s1 and β casein loci have been used for selection in breeding programs in some French and Spanish breeds [4,55,74,91,97,99].…”
Section: Current Perspective On the Impact Of Goat Casein Polymorphismmentioning
confidence: 99%